The quantitative analysis of tungsten ore using X-ray microCT: Case study. (December 2015) - Le Roux, Stephan G.; Du Plessis, Anton; Rozendaal, Abraham
Abstract: Volumetric quantification of ore minerals is of interest using non-destructive laboratory X-ray tomography, as it allows high throughput, fast analysis, without any/limited sample preparation. This means traditional chemical analysis can still be performed on the same samples, but good information can be provided in a very short time assisting in exploration, mining and beneficiation decision making as well as sample selection for further chemical analysis. This paper describes a case study in which tungsten WO3 /scheelite is quantified in 35 mm diameter drill core samples and compared to subsequent traditional chemical analysis for the same samples. The results show a good correlation and indicates that laboratory X-ray CT scanning could replace the more time consuming traditional analytical methods for ore grading purposes in some types of deposits. Different image processing methods are compared for these samples, including an advanced thresholding operation which reduces operator input error. The method should work equally well for other types of ore minerals in which the mineral of interest is the most dense particle in the scan volume, and for which the bulk of the particle sizes are at least 3 times larger than the scan resolution. Highlights: Performing X-ray microCT scans on drill core samples containing tungsten. Using the microCT data to quantify the grade of tungsten ore non-destructively. Illustrating the advantage of local threshold segmentation over global threshold. Correlating the microCT ore grade results to the industry standard results.